2012
DOI: 10.1155/2012/190950
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Degradation of PHBV Scaffolds and nHA/PHBV Composite Scaffolds Containing Hydroxyapatite Nanoparticles for Bone Tissue Engineering

Abstract: This paper investigated the long-termin vitrodegradation properties of scaffolds based on biodegradable polymers and osteoconductive bioceramic/polymer composite materials for the application of bone tissue engineering. The three-dimensional porous scaffolds were fabricated using emulsion-freezing/freeze-drying technique using poly(hydroxybutyrate-co-hydroxyvalerate) (PHBV) which is a natural biodegradable and biocompatible polymer. Nanosized hydroxyapatite (nHA) particles were successfully incorporated into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 29 publications
5
56
0
1
Order By: Relevance
“…The crystallinity of the P(3HO‐ co ‐3HHX) scaffold was decreased after composite formation indicating that crystal structures of both P(3HO‐ co ‐3HHX) and HA have changed after composite formation. Similarly, it was reported that addition of HA particles has led to lower degree of crystallinity of the PHBV matrix in composite scaffold . The XRD peaks, (211) and (300) were shifted to higher 2θ values in case of P(3HO‐ co ‐3HHX)/HA composite as compared to pure HA (i.e.…”
Section: Resultsmentioning
confidence: 63%
“…The crystallinity of the P(3HO‐ co ‐3HHX) scaffold was decreased after composite formation indicating that crystal structures of both P(3HO‐ co ‐3HHX) and HA have changed after composite formation. Similarly, it was reported that addition of HA particles has led to lower degree of crystallinity of the PHBV matrix in composite scaffold . The XRD peaks, (211) and (300) were shifted to higher 2θ values in case of P(3HO‐ co ‐3HHX)/HA composite as compared to pure HA (i.e.…”
Section: Resultsmentioning
confidence: 63%
“…Blending of PHB with HA resulted in enhanced osteoblastic response compared to pure PHB owing to increased surface roughness and porosity . Scaffolds fabricated using an emulsion‐freezing/freeze‐drying technique was found to possess uniform pore structures with average pore sizes of 297 and 210 µm and porosity of 77 and 83% for PHBV and the PHBV/10% (w/w)HA composite respectively which were optimum features for osteoblasts . As reported previously, osteoblasts have a preferred pore size ranging from 200 to 400 pm diameter for enhanced migration, attachment and proliferation since the curvature of these pores provides optimum compression and tension on the cell's mechanoreceptors .…”
Section: Bone Tementioning
confidence: 53%
“…Nanofibrous scaffolds were blotted dry with tissue paper to remove excess water and weighted. Water uptake of nanofibrous scaffolds was calculated using the following equation 1 [12].…”
Section: Methodsmentioning
confidence: 99%